PROFIL PEMAHAMAN MATEMATIS SISWA KELAS VIII A MTs AL-IKHLAS SIPAYO DALAM MENYELESAIKAN MASALAH FUNGSI DITINJAU DARI KEMAMPUAN MATEMATIKA: Mathematical Understanding Profile Of Class VIII A Students At Mts Al-Ikhlas Sipayo In Solving Function Problems Viewed From Mathematics Ability - Nizrah; Hasbi, Muh.; Murdiana, I Nyoman (Universitas Tadulako, 2023)
This research aims to obtain a description of the mathematical understanding of grade VIII A students at MTs Al-Ikhlas Sipayo in solving function problems in view of mathematical ability. This research was designed by using qualitative research. The subjects were consisted of 3 students who had high, intermediate and low abilities. Data were collected through test and interview methods. The results showed: 1) on the indicator of restating the concept of function, high and intermediate mathematics ability students can restate the concept of function correctly. Low math ability students were unable to restate the concept of function. 2) on the indicator of classifying functions according to certain properties in accordance with the function concept, high and moderate mathematics ability students can mention the function properties correctly. Low ability students could not mention the properties of functions. 3) on the indicator of giving examples of functions and not examples of functions, high mathematics ability students can give examples of functions correctly. Students with medium and low math ability could not give examples of functions. 4) on the indicator of serving function problems in the form of mathematical representations, students with high, medium, and low mathematical abilities were able to present functions in the form of mathematical representations. 5) on the indicator of using, utilizing and selecting certain procedures or operations, high and medium mathematics ability students are able to use, utilize and select certain procedures or operations, whereas low mathematics ability students are unable.